Trust, privacy and security in digital business : 12th International Conference, TrustBus 2015, Valencia, Spain, September 1-2, 2015, Proceedings /: 12th International Conference, TrustBus 2015, Valencia, Spain, September 1-2, 2015, Proceedings. (2015) - Unknown
No abstract available